HUBUNGAN SISTEM BAGI HASIL DI LEMBAGA KEUANGAN SYARIAH TERHADAP KEINGINAN NASABAH UNTUK BERINVESTASI Survei di Baitul Maal wat Tamwil (BMT) Safinah Klaten - Suyatmin, Suyatmin; Arifin, Atwal (Benefit: Jurnal Manajemen dan Bisnis, 2008)
This study aims to analyze the profit sharing system of Syariâah Financial OrganizationÂ withÂ theÂ clientsâ attitudeÂ in doingÂ an investmentÂ andÂ knowÂ whetheror thereÂ is anÂ opportunityÂ for developingÂ it. Thestatistic analysisÂ usedÂ the productÂ momentwithÂ the questionnairesÂ for the clientsÂ of Baitul Maal wat TamwilÂ SAFINAH Klaten.Â TheÂ correlationÂ of the profit sharing and doing-an-investment was significant. It could be concluded that the peopleâs confident level in the system applied to the organization was very significant. Thus, more and more clients from year to year, it is possible that there will be an opportunity for developing it.